2022
DOI: 10.1017/s1047951121005278
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of recurrent laryngeal nerve injury resulting in vocal cord paralysis following interventional congenital catheterisation procedures

Abstract: Background: Recurrent laryngeal nerve injury leading to vocal cord paralysis is a known complication of cardiothoracic surgery. Its occurrence during interventional catheterisation procedures has been documented in case reports, but there have been no studies to determine an incidence. Objective: To establish the incidence of left recurrent laryngeal nerve injury leading to vocal cord paralysis after left pulmonary artery stenting, patent ductus arteriosus device closure and the combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…A particular complication of LPA stenting in the presence of a PDA device is the occurrence of vocal cord paralysis due to impingement of the left recurrent laryngeal nerve between the device and the LPA stent [ 27 ]. In a retrospective study regarding vocal cord paralysis after LPA stenting and/or PDA device closure, involving 5364 patients in 12 institutions, this complication was seen in 2/4001 cases of PDA device closure, in 6/1337 cases of LPA stenting, and in 4/26 cases of PDA device closure + LPA stenting (15%), with most of the cases recovering completely [ 28 ]. In our series, this complication was suspected in two patients, but symptoms were mild and transitory, so no further tests or particular management was considered necessary.…”
Section: Discussionmentioning
confidence: 99%
“…A particular complication of LPA stenting in the presence of a PDA device is the occurrence of vocal cord paralysis due to impingement of the left recurrent laryngeal nerve between the device and the LPA stent [ 27 ]. In a retrospective study regarding vocal cord paralysis after LPA stenting and/or PDA device closure, involving 5364 patients in 12 institutions, this complication was seen in 2/4001 cases of PDA device closure, in 6/1337 cases of LPA stenting, and in 4/26 cases of PDA device closure + LPA stenting (15%), with most of the cases recovering completely [ 28 ]. In our series, this complication was suspected in two patients, but symptoms were mild and transitory, so no further tests or particular management was considered necessary.…”
Section: Discussionmentioning
confidence: 99%
“…It is intriguing that also in this study, 92% of the patients showed resolution of symptoms; the only persistent vocal cord paralysis was observed in one patient who underwent LPA stent placement. 26 Dalili et al reported on interventional PDA closure by using radiofrequency ablation. In two out of six patients, a transient vocal cord palsy was detected.…”
Section: Discussionmentioning
confidence: 99%